PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BIRO HUBUNGAN MASYARAKAT KEMENTERIAN PERINDUSTRIAN RI - Sophia Nursauli Sitompul (2021)
The research was conducted with the aim of knowing and proving the effect of competence and work discipline on the performance of employees of the Public Relations Bureau of the Ministry of Industry of the Republic of Indonesia, totaling 48 people. The sample technique used is Non Probability Sampling with saturated sample types. Media assistance in data processing using SPSS Version 25 using the T test and F test, so that the results can be known and proven statistically that: (1) Competence of employees of the Public Relations Bureau of the Ministry of Industry of the Republic of Indonesia has a significant positive effect on the resulting performance, (2) ) Work discipline of employees of the Public Relations Bureau of the Ministry of Industry of the Republic of Indonesia has a significant positive effect on the resulting performance, (3) Competence and work discipline of employees of the Public Relations Bureau of the Ministry of Industry of the Republic of Indonesia have a significant positive effect simultaneously on the resulting performance.